Diuraphis noxia biotypes ascribed through genotypic characterization and utilization of their endosymbiont, buchnera aphidicola - Burger, Nicolaas Francois Visser (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.